Peran Komite Audit dalam Memoderasi Pengaruh Asimetri Informasi, Leverage dan Target Keuangan terhadap Manajemen Laba - Saputra, Muhammad Ridho; Azmi, Ika Nur; Rusliyawati, Rusliyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the moderating role of the audit committee within the Indonesian banking sector concerning the influences of information asymmetry, leverage, and financial targets on earnings management. Utilizing SPSS 26, the research conducts Moderated Regression Analysis (MRA) on secondary data derived from the financial statements of the top ten banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The results demonstrate that leverage (p=0,001) significantly increases earnings management. Conversely, stringent regulations by Indonesia's Financial Services Authority (OJK), which promote transparency, explain why information asymmetry (p=0,407) and financial targets (p=0,075) exhibit no discernible impact. An efficient audit committee mitigates the effect of financial targets (p=0,046) on earnings management. However, due to structural complexity and monitoring limitations, the audit committee fails to directly moderate the influence of information asymmetry (p=0,506) and leverage (p=0,185). These findings support agency theory and signaling theory. The study recommends that audit committees adopt a more practical role in scrutinizing information asymmetry, leverage, and financial targets to constrain earnings manipulation risks.